The roles of soybean lecithin in aquafeed: a crucial need and update - Wee, Wendy; Téllez-Isaías, Guillermo; Abdul Kari, Zulhisyam; Cheadoloh, Romalee; Kabir, Muhammad Anamul; Mat, Khairiyah; Mohamad Sukri, Suniza Anis; Rahman, Mohammad Mijanur; Rusli, Nor Dini; Wei, Lee Seong (Frontiers in Veterinary Science, 2023)
Soybean lecithin is extensively used as the dietary supplementation of phospholipids in animal production. Soybean lecithin plays significant roles in aquafeed as growth promoter, feed enhancer, immunity modulator and antioxidant activity stimulator for aquaculture species. Besides, soybean lecithin is also reported to help aquaculture species being resilient to physical and chemical stressors. In this review, common sources, chemical structure and mode of action of lecithin, with highlight on soybean lecithin application in aquaculture over four-decadal studies published between 1983 and 2023, were evaluated and summarized. By far, soybean lecithin is best-known for its beneficial effects, availability yet cost-effective for aquafeed formulation. Findings from this review also demonstrate that although nutritional profile of long-chain polyunsaturated fatty acids and phosphatidylcholine from egg yolk and marine sources are superior to those from plant sources such as soybean, it is rather costly for sustainable application in aquafeed formulation. Moreover, commercially available products that incorporate soybean lecithin with other feed additives are promising to boost aquaculture production. Overall, effects of soybean lecithin supplementation are well-recognized on larval and juvenile of aquaculture species which having limited ability to biosynthesis phospholipids de novo, and correspondingly attribute to phospholipid, a primary component of soybean lecithin, that is essential for rapid growth during early stages development. In addition, soybean lecithin supplementation plays 2 This is a provisional file, not the final typeset article a distinguish role in stimulating maturation of gonadal development in the adults, especially for crustaceans.